THE ANALYSIS OF FLIGHT FREQUENCY ON ROUTE JAKARTA - ISTANBUL CONNECTING TO OTHER CITIES TO COVER MARKET DEMAND - Hendri Sepriandi; Lita Julianti Putri; Tito Warsito (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
The purpose of this research is to analyse the flight frequency required for Turkish Airlines on 2018-2019. The problem of the research is the route of Jakarta-Istanbul that is used for Umrah and Leisure often have overbooked due  to Turkish Airlines only provide one flight per day to carry all passengers. The methodology used quantitative descriptive analysis with the least square method to estimate the trend value that will be used as a tool to forecast the number of passengers. Seasonal variations in the data are regular upward or downward movements in a time series that tie to recurring events. The result of the data recorded in 2016 the average load factor reached by airlines of Turkey was 83.48%, aircraft seat capacity and inadequate and therefore cannot meet the demand of passengers, as well as using airline indicator calculation to analyse the flight frequency needs. It is resulted that the total passenger in 2018-2019 will increase, where in 2018 is in amount of 110.612 passengers and in 2019 is in amount of 125.645 passengers. Turkish Airlines needs to add 1 time flight frequency in a particular day on that route.